A study of lithosphere-ionosphere coupling using TUSAGA active TEC estimates - Karatay, Seçil; Arikan, Feza; Arikan, Orhan; Sayin, Işiltan; Aysezen, Melih Ş.; Lenk, Onur; Aktu?, Bahadir (My University, 2010)
In this study, the disturbances in the ionosphere due to the seismic activity are investigated by using Total Electron Content estimates obtained from TUSAGA Active GPS stations in Turkey. Two earthquakes with same geophysical properties occurred on Northern Anatolia Fault are chosen for the study. TEC estimates are compared with each other using correlation coefficient (IK), symmetric Kullback-Leibler Distance (KLD) and L2-Norm (L2N) for geomagnetically and seismically quiet days of ionosphere and the earthquakes days. It is observed that IK values of quiet days are highly correlated in quiet days. IK values of earthquake days decrease down to 0.2 in earthquake days. KLD values of earthquake days are 10 times greater than those of the quiet days. In order to form a proper earthquake precursor alarm signal, more earthquakes with different properties have to be investigated in the future. ©2010 IEEE.
Litosfer-i?yonosfer ba?laşiminin TUSAGA aktif TEİ kestirimleri i?le i?ncelenmesi
18th IEEE Signal Processing and Communications Applications Conference, SIU 2010 -- 22 April 2010 through 24 April 2010 -- Diyarbakir -- 83388
Keywords: Estimation; Ionosphere; Ionospheric measurement; Signal processing; Alarm signals; Correlation coefficient; Earthquake precursors; Geophysical properties; Highly-correlated; Kullback-Leibler distance; L2-norm; Seismic activity; Total electron content; Earthquakes